Social Capital and Mobility: An Experimental Study - Rostislav Staněk; Ondřej Krčál; Štěpán Mikula (Masaryk University, Faculty of Economics and Administration, 2021)
Theoretical models of social capital (David, Janiak, and Wasmer 2010; Bräuninger and Tolciu 2011) predict that communities may find themselves in one of two equilibria: one with a high level of local social capital and low migration or one with a low level of local social capital and high migration. There is empirical literature suggesting that immigrants who join communities high in social capital are more likely to invest in local social capital and that the whole community will then end up in the equilibrium with high local social capital and low migration. However, this literature suffers from the selection of immigrants, which makes the identification challenging. In order to test the causal influence of the initial level of local social capital, we take the setup used in the theoretical models into the laboratory. We treat some communities by increasing the initial level of social capital without affecting the equilibrium outcomes. We find that while most communities end up in one of the two equilibria predicted by the theoretical models, the treated communities are more likely to converge to the equilibrium with a high level of local social capital and low migration.
Keywords: C92; J15; 330; social capital; integration; equilibrium selection; laboratory experiment